Role of Cerebro-Placental Ratio in prediction of adverse perinatal outcome in hypertensive disorder of pregnancy - Giri, Amrita; Shrestha, Amit; Joshi, Anshumala (Nepal Medical College Journal, 2022)
Hypertensive disorder of pregnancy is a multisystem disorder associated with an increased risk of perinatal mortality worldwide. Doppler velocimetry of uterine, umbilical, and fetal vessels is an established method of antenatal monitoring identifying fetus at risk. The cerebroplacental ratio (CPR) is emerging as an important predictor of the adverse perinatal outcome as it considers both umbilical and middle cerebral artery doppler. The aim of this study is to find the role of CPR in the prediction of adverse perinatal outcome in the hypertensive disorder of pregnancy. A prospective descriptive study was done on women admitted to a tertiary care hospital in Kathmandu from July 2020 to June 2021 after taking ethical clearance from Institutional Review Committee. A total of 136 hypertensive pregnant women beyond 34 weeks of gestation underwent Doppler ultrasound, and CPR ratio <1.08 (done within one week of delivery) was considered abnormal. During the study, CPR was normal in 101 women (74.3%) and was abnormal in 35 women (25.7%). The study showed that the rate of cesarean section was high in women with abnormal CPR than with normal CPR (77.1% vs 45.5%). The caesarean section done for fetal distress (70.4% vs 39.1%), Apgar score < 7 in 5 minutes (14.3% vs 3.0%), NICU admission rate (54.3% vs 27.7%), and duration of NICU stay (3.9 + 4.08 vs 0.79 +1.94 days) were high in women with abnormal CPR. The cerebroplacental ratio in hypertension in pregnancy can provide useful information regarding fetal well-being and help us in improving fetal outcomes.